2018
DOI: 10.1016/j.jcm.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Dietary Fiber Intake on Reducing the Risk of Cancer: An Umbrella Review of Meta-analyses

Abstract: This review suggests that those consuming the highest amounts of dietary fiber may benefit from a reduction in the incidence of developing colorectal cancer, and there also appears to be a small reduction in the incidence of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 43 publications
2
31
0
2
Order By: Relevance
“…Fiber: A review of all published meta-analyses was performed on the association between dietary fiber and colorectal cancer conclude that the high consumption of fiber may benefit from a reduction in the incidence of developing colorectal cancer [67]. High-fiber content has many roles, including diluting and binding potential carcinogens as well as reducing transit time [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Fiber: A review of all published meta-analyses was performed on the association between dietary fiber and colorectal cancer conclude that the high consumption of fiber may benefit from a reduction in the incidence of developing colorectal cancer [67]. High-fiber content has many roles, including diluting and binding potential carcinogens as well as reducing transit time [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of dietary fibre in the prevention of colorectal cancer remains controversial. However, studies conducted on large population samples showed that high intakes of dietary fibre, especially from grains, cereals, and whole grain cereal foods are associated with reduced risks of colorectal [23,28,39,40,41,42] and gastric cancer [33,41]. Many other studies strengthen the evidence for dietary fibre protective role in the prevention of colon and/or rectum cancer [43,44,45,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, dietary factors [7] may affect the risk of esophageal cancer. Previous studies suggested that vitamins intake [8,9], fiber intake [10], folate intake [11,12], could decrease the development of esophageal cancer. Intakes of bioactive compounds from various plant sources also reduced the risk of cancer [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%